Profitability, Leverage, Firm Size, Liquidity, and Total Assets Turnover on Real Earnings Management (An Empirical Study on the Mining Company Classification Registered at Indonesia Stock Exchange (IDX) 2014-2017) - Adi, Suyatmin Waskito; Putri, Wulanditya Anggun Permata; Permatasari, Widowati Dian (Universitas Muhammadiyah Surakarta, 2020)
The aim of this research is to analyze the effect of profitability, leverage, firm size, liquidity, and total assets turnover on real earnings management. The population of this research is the classification of mining companies listed on the Indonesia Stock Exchange (IDX) in 2014-2017. The sampling method used a purposive sampling method and obtained as many as 80 companies. The data analysis method used multiple linear regression method. The results showed that the total asset turnover affected real earnings management. While profitability, leverage, firm size, and liquidity did not affect real earnings management.